2021
DOI: 10.1007/s11430-020-9733-1
|View full text |Cite
|
Sign up to set email alerts
|

The big mantle wedge and decratonic gold deposits

Abstract: The Circum-Pacific subduction zone is a famous gold metallogenic domain in the world, with two important gold metallogenic provinces, the North China Craton and Nevada, which are related to the destruction of the North China Craton and the Wyoming Craton, respectively. Their ore-forming fluids were possibly derived from the stagnant slab in the mantle transition zone. The oceanic lithospheric mantle usually contains serpentine layers up to thousands of meters thick. During plate subduction, serpentine is dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 109 publications
0
24
0
Order By: Relevance
“…10.1029/2019RG000689 formation of lithospheric properties from a refractory, enriched mantle to a fertile, depleted mantle (Tang et al, 2021, and references therein), formation of large oil and gas reservoirs, and explosive gold mineralization (Zhu et al, 2015(Zhu et al, , 2017Zhu & Sun, 2021). Compared with other cratons globally, the NCC is the best example of craton destruction.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…10.1029/2019RG000689 formation of lithospheric properties from a refractory, enriched mantle to a fertile, depleted mantle (Tang et al, 2021, and references therein), formation of large oil and gas reservoirs, and explosive gold mineralization (Zhu et al, 2015(Zhu et al, , 2017Zhu & Sun, 2021). Compared with other cratons globally, the NCC is the best example of craton destruction.…”
Section: Tablementioning
confidence: 99%
“…The following processes mark craton destruction: the extensive volcanic eruption and granitic emplacement (Ma & Xu, 2021, and references therein), intensive lithospheric extension, thinning, crustal deformation, and rift-basin formation, all of which indicate that the cratonic lithosphere has been destabilized (Zhu et al, 2020, and references therein). Notably, the destruction of a craton is also accompanied by the trans-formation of lithospheric properties from a refractory, enriched mantle to a fertile, depleted mantle (Tang et al, 2021, and references therein), formation of large oil and gas reservoirs, and explosive gold mineralization (Zhu et al, 2015(Zhu et al, , 2017Zhu & Sun, 2021). Compared with other cratons globally, the NCC is the best example of craton destruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tectonic regime transformation and crustal activation appeared in the NCC during Mesozoic, and the thinning of the lithosphere and the appearance of voluminous crust-derived granites were the main characteristics [28]. Previous studies have shown that the destruction of the craton and the Mesozoic magmatism in eastern North China are closely related to the subduction of the paleo-Pacific plate [29][30][31]. Since the Early Jurassic, the paleo-Pacific plate has changed from a low-angle subduction to a high-angle subduction, accompanied by the retreat of the subduction zone, which induced strong destruction in the eastern part of the NCC.…”
Section: Geological Settingmentioning
confidence: 99%
“…Minerals 2021, 11, x FOR PEER REVIEW 3 of 14 in eastern North China are closely related to the subduction of the paleo-Pacific plate [29][30][31]. Since the Early Jurassic, the paleo-Pacific plate has changed from a low-angle subduction to a high-angle subduction, accompanied by the retreat of the subduction zone, which induced strong destruction in the eastern part of the NCC.…”
Section: Geological Settingmentioning
confidence: 99%